Research on Drilling Technology Methods and Application Effects in Geological Engineering Exploration - Yang, Yifei; Yuan, Zongxing (Scientific Journal of Technology, 2025)
Drilling technology is one of the core means of geological engineering exploration. This article systematically reviews the commonly used technical methods in geological engineering exploration, such as rotary drilling, impulse drilling, vibratory drilling, hydraulic rotary drilling, and pneumatic drilling. It focuses on analyzing the principles, characteristics, applicable conditions, and existing problems of each type of drilling technology. On this basis, the application status of drilling technology in geotechnical engineering investigation, hydrogeological investigation, mineral resource exploration and other fields was further explored. The exploration accuracy and quality, efficiency and cost, environmental impact, etc. of drilling technology were systematically evaluated, and corresponding optimization countermeasures and suggestions were put forward, with the aim of providing references for improving the level of drilling technology and better serving the practice of geological engineering exploration.